Features of the Development of the Navoi Tourism Circle in the Diversification of the Tourism Market of the Central Tourism Region - Abdukhamidov Sarvar Adhamovich (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Tourism development and diversification play an important role in supporting regional economic stability, employment creation, and cultural exchange within modern tourism systems. Specific Background: The Navoi region of Uzbekistan possesses significant tourism potential due to its historical monuments, natural landscapes, pilgrimage sites, and favorable transport and logistics infrastructure, which create opportunities for expanding tourism activities. Knowledge Gap: Despite this potential, the structural development and functional role of the Navoi Tourism Ring in supporting diversification of the regional tourism market have not been sufficiently examined in academic studies. Aims: This study aims to analyze the development characteristics of the Navoi Tourism Ring and to examine its role in expanding tourist routes and tourism infrastructure in the Central Tourism Region. Results: The findings show that in 2024 the region experienced a sharp increase in tourist arrivals, reaching 420.2 thousand foreign visitors and 2.485 million domestic tourists, while tourism exports reached 105 million USD. The implementation of the tourism ring concept led to the creation of 14 tourist routes covering 60 tourism facilities across several districts, along with infrastructure expansion including new hotels, increased accommodation capacity, and tourism clusters offering desert experiences and cultural activities. Novelty: The study highlights the structural organization of tourism routes and infrastructure development within the Navoi Tourism Ring as a regional diversification mechanism. Implications: The development of integrated tourist routes, infrastructure expansion, marketing strategies, and professional training contributes to strengthening the tourism sector, promoting cultural heritage, and supporting sustainable regional tourism development. Highlights:• Rapid Growth of Visitor Numbers and Tourism Export Value Recorded in 2024.• Fourteen Integrated Routes Connecting Sixty Attractions Across Multiple Districts.• Tourism Clusters Provide Desert Experiences, Cultural Heritage Visits, and Accommodation Services. Keywords: Tourism Diversification, Navoi Tourism Ring, Regional Tourism Development,Tourist Routes, Tourism Infrastructure.